Electrodeless Reverse Electrodialysis Patches as an Ionic Power Source for Active Transdermal Drug Delivery. (22nd January 2018) - Kwon, Seung‐Ryong; Nam, So Hee; Park, Clara Yongjoo; Baek, Seol; Jang, Joomyung; Che, Xiangguo; Kwak, Su Hong; Choi, Yu‐Ra; Park, Na‐Rae; Choi, Je‐Yong; Lee, Yan; Chung, Taek Dong
Abstract: Reverse electrodialysis (RED) is one of the promising sustainable technologies generating electric power from the mixing energy of two different salt solutions. Most of the reports on the RED systems are focused on scale‐up development and the improvement of maximum power density. However, regarding biocompatible and eco‐friendly natures, the RED system also has a great potential use where low electrical power is necessary, in particular for skin‐wearable biomedical devices. In this work, electronics‐free RED patches are devised as an ionic power source for active transdermal drug delivery. The electrodeless RED patches generate reliable voltages, which are proportional to the number of ion‐exchange membranes and salinity ratios, and successfully facilitate in vitro delivery of ionic drugs through mouse skin without involving any electronic component for the first time; 9, 20, and 36‐fold increases with lidocaine, ketorolac, and risedronate, respectively. Indeed, by using an osteoporosis‐induced mouse model, the RED patch delivery demonstrates powerful in vivo therapeutic effects against the diffusion‐based topical administration. The new ionic power source can allow transport of various types of drugs in the transdermal route and, more importantly, can be used for the operation of other portable biomedical devices. Abstract : Electronics‐free reverse electrodialysis patches as an ionic power source are devised to introduce a new concept of transdermal drug delivery system. The ionic power source efficiently delivers ionic drugs through skin layers by generating an appropriate electric power and can be used for the operation of other biomedical devices such as wearable sensors.